(untitled) - Turner, Monica G (New York, 1991)
This book seeks to meet this need by providing a conceptual framework and illustrating potential applications for methods such as pattern analysis, spatial statistics, fractals, spatial modelling, broad-scale studies, and extrapolation across scales
Keywords: lanscape ecology,lanscape ecology; methodology,simulation methods